2006
DOI: 10.1016/j.tecto.2005.10.046
|View full text |Cite
|
Sign up to set email alerts
|

GPS results for Macedonia and its importance for the tectonics of the Southern Balkan extensional regime

Abstract: GPS results from 25 stations in Macedonia measured in 1996 and 2000 show that Macedonia moves SSE relative to Eurasia essentially as a single crustal piece along with parts of westernmost Bulgaria. Geological studies show active N-S normal faults and two NNW-striking right-lateral faults in western Macedonia, and NW-trending left-lateral faults SE Macedonia, with a region in central Macedonia essentially devoid of active faults. Distribution of seismic activity supports the geological studies. However, the GPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 12 publications
3
26
0
1
Order By: Relevance
“…At its western end, segment A runs to the north of the regions of extension and convergence in Greece. Although there is some active deformation to the north of this line, velocities there are generally lower than 2–3 mm/yr relative to Eurasia [ Burchfiel et al , ; Kotzev et al , ].…”
Section: Physical Modelmentioning
confidence: 99%
“…At its western end, segment A runs to the north of the regions of extension and convergence in Greece. Although there is some active deformation to the north of this line, velocities there are generally lower than 2–3 mm/yr relative to Eurasia [ Burchfiel et al , ; Kotzev et al , ].…”
Section: Physical Modelmentioning
confidence: 99%
“…Northeastern Aegean Sea is affected by dextral active strike‐slip related to the NAF (∼25 mm/yr [ McClusky et al , 2000]). In the Balkan Peninsula, geodetic data suggest small but still active N‐S extension [ Burchfiel et al , 2006], emphasized by historic seismic activity in Bulgaria revealed by morphotectonic and paleoseismic studies [ Meyer et al , 2007]. High seismic activity and transpression on the active Kefalonia Fault is well documented [ Louvari et al , 1999].…”
Section: Tectonic Settingsmentioning
confidence: 99%
“…Previous kinematic and geodynamic works have focused either on Central or Eastern Mediterranean, and little effort has been made to produce a self‐consistent kinematic solution that simultaneously fits Calabria and Hellenic geodetic data as well as onshore and offshore constraints. Deformation in the Balkans [ Burchfiel et al , 2006; Kotzev et al , 2006], emphasized by recent GPS studies [ Jouanne et al , 2012; K. Matev et al, Horizontal movements and strain rates obtained from GPS observations for the period 1996–2008 in southwest Bulgaria and northern Greece, manuscript in preparation, 2012] (Figure 2), has not always been considered, while fragmentation of the Nubian plate [ D'Agostino et al , 2008] is generally neglected.…”
Section: Introductionmentioning
confidence: 99%
“…This lead to the reactivation of inherited faults and subsequently pull apart-like opening of the Ohrid Basin (Dumurdzanov et al 2005;Ilic and Neubauer, 2005). After Burchfiel et al (2006), the recent transition zone (today located in Central Albania) between extensional and the compressional regime is evidently marked by right-lateral strike-slip, which can be identified from displacement vectors derived from GPS measurements and geological data. Concerning the westward migration of the deformation domains as explained in Chap.…”
Section: Tectonic Historymentioning
confidence: 99%